SERVANT LEADERSHIP, MOTIVATION, AND TRAINING IN VOLUNTEER PERFORMANCE THROUGH LOYALTY AS INTERVENING VARIABLES - Rahmatulloh Gustiamtomo; Firdaus, Vera (Journal of Social Science, 2025)
Objective: The purpose of this research is to determine the influence of variables such as Servant Leadership, Training, and Motivation on the Performance of MRI (Masyarakat Relawan Indonesia) volunteers, with Loyalty as the intervening variable. Method: The population of this study consisted of 198 individuals. Non-probability sampling technique, specifically purposive sampling, was used, resulting in a sample size of 132 individuals. Data were collected using a questionnaire with measurement instruments employing a Likert scale. The data were analyzed using multiple regression analysis, and the Sobel test was utilized to determine the mediating effect of variables. Results: The research findings indicate a positive and significant partial influence of Servant Leadership, Motivation, Training, and Loyalty on Volunteer Performance. Additionally, there is a positive and significant partial influence of Servant Leadership, Motivation, and Training on Volunteer Loyalty. It was also observed that the variable of loyalty can mediate the relationship between Servant Leadership, Motivation, and Training, and Volunteer Performance. Novelty: This study provides empirical evidence on the mediating role of loyalty in the relationship between Servant Leadership, Motivation, and Training with volunteer performance in the context of MRI (Masyarakat Relawan Indonesia), which has been less explored in existing volunteer management literature.